NATIONAL TRADITIONS IN SPIRITUAL DEVELOPMENT FUTURE TEACHERS - Klepar, Maria (Mountain School of Ukrainian Carpaty, 2021)
It was concluded that knowledge concerning spiritual achievements gained by young people during their studies should make stimulant active treatment of young Ukrainian to study specific in nature, truly accurate historical spiritual heritage of his people, rooted in folklore (folk art) and saved in any manifestation at the local level. The article analyzes the role of national traditions in the spiritual development of future teachers. The specific focus is placed on the problems of primary school. According to scientists, it is in the early school years that the worldview of the individual is formed, in particular the national identity. The upbringing of a versatile and harmonic personality of a petty in the new age Ukrainian school is one of the most important tasks at the present stage of society; in which enrichment of the child's spiritual world involves the formation of creative potential and inner culture as well as spiritual unity of generations. The upbringing of young citizens should be aimed primarily at developing their humanistic feelings, the formation of national and universal values. Therefore, the revival of folk song culture has great importance in the education of students of the new age Ukrainian school. The educational possibilities of Ukrainian folk songs were determined in the theoretical analysis. The necessity of directing the attention of the petty on the ideological and didactic nature of the folk song was described. That is important as the song folklore is a polysystemic means of personality formation, and it affects the spiritual, intellectual, emotional, and other spheres of a human being; morally and psychologically adjusts a person to work. The proper use of ethno –pedagogical tools ensures the esthetic development of students along with a high culture of perception of various arts. In conclusion, the knowledge of spiritual achievements gained by petty during their studies should stimulate an affirm attitude of them as young Ukrainians to study and research historical, spiritual heritage of their people, the roots of which are folklore (folk art) that is preserved in different manifestations at the local levels.